Occurrence of strains producing specific antibacterial inhibitory agents in five genera of Enterobacteriaceae - Šmarda, Jan; Šmajs, David; Lhotová, Hana; Dědičová, Daniela (Current microbiology, 2007)
Striking differences in the production of specific inhibitory agents affecting other strains of the same (or of related) species were found between genera of the family Enterobacteriaceae. We tested 50-163 strains each of the potentially pathogenic genera: Escherichia, Citrobacter, Enterobacter, Kluyvera, and Leclercia for their ability to produce bacteriophages, high-molecular-weight (HMW) and low-molecular-weight (LMW) bacteriocins and siderophores against the same sets of strains, using the cross-test method. The genus Escherichia differs substantially from all other Enterobacteriaceae, harboring a notable proportion of lysogenic (36.6%) and colicinogenic (13.9%) strains. Only 18.2% of the Citrobacter strains are lysogenic and only rarely are they colicinogenic, although in 7.3%, they produce phage tail-like bacteriocins. On the other hand, Kluyvera strains were only in 1.8% lysogenic, no colicinogenic strains were found, but in 7.3%, they produced siderophores causing zones of growth inhibition in agar cultures of strains of the same genus. In Leclercia, 10.0% of the strains were lysogenic, 2.0% produced HMW bacteriocins, no colicinogenic strains were found and 2.0% produced siderophores. Enterobacter has shown 23.1% of strains producing siderophores, whereas merely 7.7% were lysogenic, 1.9% colicinogenic and 3.8% formed phage tail-like bacteriocins. HMW bacteriocins of Enterobacter strains disposed of an unusually wide spectrum of activity. The siderophore activity spectrum was rather wide in any genus, but the siderophores were usually not produced by strains producing phages or colicins.
Keywords: financování organizované; siderofory; Bacteriocins; lidé; Anti-Bacterial Agents; Bacteriophages; Culture Media; Financing, Organized; lyzogenie; Incidence; molekulová hmotnost; kultivační média; incidence; Colicins; bakteriociny; koliciny; Siderophores; Lysogeny; Molecular Weight; antibakteriální látky; bakteriofágy; Enterobacteriaceae; Humans